2020
DOI: 10.4049/jimmunol.1901299
|View full text |Cite
|
Sign up to set email alerts
|

Vinpocetine Suppresses Streptococcus pneumoniae–Induced Inflammation via Inhibition of ERK1 by CYLD

Abstract: Otitis media (OM) is the most common bacterial infection in children. It remains a major health problem and a substantial socioeconomic burden. Streptococcus pneumoniae (S. pneumoniae) is one of the most common bacterial pathogens causing OM. Innate inflammatory response plays a critical role in host defense against bacterial pathogens. However, if excessive, it has a detrimental impact on the middle ear, leading to middle ear inflammation, a hallmark of OM. Currently, there has been limited success in develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
(115 reference statements)
0
5
0
Order By: Relevance
“…Recent studies, including our own, have suggested that A20 participates in the pathogenesis of periodontitis (Crump et al., 2017; Hong et al., 2016; Mooney & Sahingur, 2020; Yan et al., 2020). Besides, A20, another negative regulator of NF‐κB signalling, is the CYLD protein, which functions as an important modulator of tumorigenesis and inflammatory responses, by inhibiting NF‐κB activation (Hrdinka et al., 2016; Komatsu et al., 2020; Lork et al., 2017; Mukherjee et al., 2020; Sato et al., 2015). Given the role of CYLD in restricting NF‐κB signalling and inflammation resolution, it is reasonable to speculate that CYLD may have an inhibitory effect on periodontal inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies, including our own, have suggested that A20 participates in the pathogenesis of periodontitis (Crump et al., 2017; Hong et al., 2016; Mooney & Sahingur, 2020; Yan et al., 2020). Besides, A20, another negative regulator of NF‐κB signalling, is the CYLD protein, which functions as an important modulator of tumorigenesis and inflammatory responses, by inhibiting NF‐κB activation (Hrdinka et al., 2016; Komatsu et al., 2020; Lork et al., 2017; Mukherjee et al., 2020; Sato et al., 2015). Given the role of CYLD in restricting NF‐κB signalling and inflammation resolution, it is reasonable to speculate that CYLD may have an inhibitory effect on periodontal inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…VNP's ability to increase cylindromatosis, a key inflammatory suppressor, and block MAPK and ERK activity, thereby decreasing S. pneumoniae -induced inflammation, clarifies these findings. 128 Likewise, Zhou and colleagues have found that VNP decreases levels of TNF-α and IL-6 cytokine peptides in murine microgliocytes challenged by LPS. 129 Notably, the medication suppresses the mRNA levels of TLR4 and TLR2 and their key signalling molecules, including the mitogen-activated protein kinase (MAPK) cascade and MYD88.…”
Section: Discussionmentioning
confidence: 98%
“…Another agent, vinpocetine, which suppresses inflammation induced by S. pneumoniae through inhibition of ERK (Ref. 99 ) reduces middle ear inflammation in a murine model of OM. To date, none of these have been trialled in human OM.…”
Section: Methodsmentioning
confidence: 99%